On the verge of insanity : Van Gogh and his illness - Bakker, Nienke, 1972-; Van Gogh Museum, Amsterdam; Meedendorp, Teio; Prins, Laura; Van Tilborgh, Louis, 1956- (Brussels : Mercatorfonds, 2016)
The mental state of Vincent van Gogh (1853-1890) has been a perennial source of discussion and conjecture since his death by suicide. Was he mentally ill or a genius? What was the precise nature of Van Gogh's illness? Did it influence his work? This intriguing publication examines how Van Gogh's mental condition revealed itself in 1888 and how he struggled with it throughout his life. Van Gogh's letters to his brother Theo, his artist friends, and his sister Willemien reveal that his primary reason for living was his art. Richly illustrated with artworks, letters, previously unpublished historical documents, and photographs, 'On the Verge of Insanity' provides a nuanced and considered overview of an extraordinary man who had to cope with mental illness at a time when the symptoms were readily misunderstood and professional treatment was insufficient. The authors also offer a detailed account of the circumstances surrounding Van Gogh's death in Auvers-sur-Oise, and they review the many diagnoses that have been proposed since the artist's death.
Foreword -- An introduction : seeking clam in the storm / Louis van Tilborgh -- Van Gogh's illness : the witnesses recall / Nienke Bakker -- Van Gogh's physical and mental health : a chronology ; What was wrong with Van Gogh? : a summary of the diagnoses / Laura Prins -- Original documents -- Bibliography -- Acknowledgements -- About the authors -- Index.
Published to accompany the exhibition, On the verge of insanity: Van Gogh and his illness
Includes bibliographical references (pages 171-172) and index.
Keywords: Gogh, Vincent van, -- 1853-1890 -- Exhibitions; Gogh, Vincent van, -- 1853-1890 -- Mental health; Gogh, Vincent van, -- 1853-1890.; 2102 history of painting; Mental health; Exhibition catalogs; Exhibition catalogs; Exhibition catalogs